Lesion-symptom mapping of self-prioritization in explicit face categorization: distinguishing hypo- and hyper-self-biases. - Sui, J; Chechlacz, M; Rotshtein, P; Humphreys, G (2015)
People make faster familiarity decisions for their own face compared with a familiar other. Lesion studies diverge on whether this self-face prioritization (SFP) effect is associated with functional processes isolated in the left or right hemispheres. To assess both decreases (hypo-) and increases (hyper-) in SFP after brain lesion, we asked patients with chronic deficits to perform familiarity judgments to images of their own face, a familiar other, or unfamiliar faces. Of 30 patients, 7 showed hypo- and 6 showed hyper-self-bias effects, comparing responses with their own faces versus responses with a familiar other. Hyper-self-bias correlated with reduced executive control function and, at a neural level, this was associated with lesions to the left prefrontal and superior temporal cortices. In contrast, reduced self-prioritization was associated with damage to the right inferior temporal structures including the hippocampus and extending to the fusiform gyrus. In addition, lesions affecting fibers crossing the right temporal cortex, potentially disconnecting occipital-temporal from frontal regions, diminished the self-bias effect. The data highlight that self-prioritized face processing is linked to regions in the right hemisphere associated with face recognition memory and it also calls on executive processes in the left hemisphere that normally modulate self-prioritized attention.